2016 Global food policy report [in Chinese] - International Food Policy Research Institute (2016)
Dr. Shenggen Fan, Director General of the International Food Policy Research Institute (IFPRI), released the 2016 Global Food Policy Report in Beijing. The report outlines the major food policy issues, developments, and decisions of 2015, and highlights the challenges and opportunities for 2016.